2015
DOI: 10.5267/j.ijiec.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

On the application of response surface methodology for predicting and optimizing surface roughness and cutting forces in hard turning by PVD coated insert

Abstract: This paper focuses on the exploitation of the response surface methodology (RSM) to determine optimum cutting conditions leading to minimum surface roughness and cutting force components. The technique of RSM helps to create an efficient statistical model for studying the evolution of surface roughness and cutting forces according to cutting parameters: cutting speed, feed rate and depth of cut. For this purpose, turning tests of hardened steel alloy (AISI 4140) (56 HRC) were carried out using PVD -coated cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…A full quadratic model was used to fit the experimental data and identify the relevant model terms using statistical software (Design Expert 9 and JMP Pro 10 software). As it is indicated by Hessainia et al [22] and Zahia et al [23], a quadratic model, which also includes the linear model, can be described as:…”
Section: Methods 221 Response Surface Methodology Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A full quadratic model was used to fit the experimental data and identify the relevant model terms using statistical software (Design Expert 9 and JMP Pro 10 software). As it is indicated by Hessainia et al [22] and Zahia et al [23], a quadratic model, which also includes the linear model, can be described as:…”
Section: Methods 221 Response Surface Methodology Approachmentioning
confidence: 99%
“…RSM can represent the direct and interactive effects of process parameters through the analysis of variance (ANOVA). Moreover, this approach applied in the present work is considered as a procedure to identify a relationship between independent input process parameters and output data (process response), which includes commonly six steps as it is indicated by Gaitonde et al [21] and Tebassi et al [20]: (1) define the independent input variables and the desired output responses, (2) adopt an experimental design plan, (3) perform regression analysis with the required model of RSM as found by Hessainia et al [22] and Zahia et al [23] as shown in Eq. (1).…”
Section: Methods 221 Response Surface Methodology Approachmentioning
confidence: 99%
“…Xi reveals the coded variables that correspond to the studied machining parameters such as cutting speed (Vc), feed rate (f) and cutting time (t), and ε is a random experimental error. The analysis of variance (ANOVA) has been applied to check the adequacy of the developed machinability models (Bouzid et al, 2015;Berkani et al 2015;Zahia et al 2015;Keblouti et al 2017). The ANOVA table consists of sum of squares and degrees of freedom.…”
Section: Rsm-techniquementioning
confidence: 99%
“…Similarly, the significant effect on cutting force components are obtained to be depth of cut; workpiece hardness and feed rate respectively. Zahia et al (2015) studied on hard turning of AISI 4140 (56 HRC) steel using PVD coated ceramic insert. Feed rate and depth of cut are found to be the most significant parameters affecting surface roughness and cutting forces from analysis of variance (ANOVA) study.…”
Section: Introductionmentioning
confidence: 99%